Research on the Use of Eye-Tracking in Marking Prohibited Items in Security Screening at the Airport - Artur Kierzkowski; Tomasz Kisiel; Ewa Mardeusz; Jacek Ryczyński (Applied Sciences)
This article presents the results of an experimental study that indicates a problem in assessing the effectiveness of security control operators, that is, the Hit Rate indicator. It was pointed out that there is a significant error in determining whether an operator correctly identifies prohibited items. This is a significant problem because the effectiveness of operators is expected to be very high, and the measurement error may interfere with their correct assessment. So far, there has yet to be any research on improving the accuracy of estimating this rate. This article examines whether eye-tracking technology can be used to eliminate this error. An experimental test of using a 120 Hz eye-tracking system was conducted to see what the effectiveness of identifying gaze location is on two 19″ monitors, which simulates the operator’s actual work environment. The tests were conducted under simulated conditions, using a replica of an actual security control operator’s station. As a contribution, it has been proven that it is possible to use eye-tracking technology to significantly increase the accuracy of screening operators’ assessments. This is important knowledge that can be the basis for further research in this area.